An IoT-based dynamic traffic management system in perspective of Bangladesh. (24th October 2019) - Sadi, Sadman Hoque; Hossin, Md. Altab; Sabuj, Saifur Rahman
This article presents a traffic management system that dynamically micro-manages city traffic by keeping track of the precise number of stationary vehicles at every intersection. It can be implemented quickly at a relatively low cost. Through the use of localised computing, a trilateration system, integration of internet of things (IoT) and development of an algorithm which manages the green signal timing on a per lane basis we create a system which is not only cost effective, but also provides vehicle security and public notification of citywide traffic congestion. It is capable of working in conjunction with both human driven vehicles of today as well as the self-driving vehicles of tomorrow. We simulate overall effectiveness of the system in MATLAB for worst-case scenario and have nonetheless found favourable (5-10% improvement) results.